2012
DOI: 10.1016/j.jml.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

When do memory limitations lead to regularization? An experimental and computational investigation

Abstract: Elsevier believes that individual authors should be able to distribute their AAMs for their personal voluntary needs and interests, e.g. posting to their websites or their institution's repository, e-mailing to colleagues. However, our policies differ regarding the systematic aggregation or distribution of AAMs to ensure the sustainability of the journals to which AAMs are submitted. Therefore, deposit in, or posting to, subject-oriented or centralized repositories (such as PubMed Central), or institutional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 99 publications
3
65
2
Order By: Relevance
“…A common hypothesis is that children's bias toward regularization might be due to their limited memory [46]. However, these accounts are hard to reconcile with other research indicating that limitations of this type do not necessarily lead to more regularization [7,8]; while it is possible that memory limitations may play a role, it seems unlikely that they are the main driving force behind this behaviour. Consistent with this, there is evidence that learners bring domain-specific biases to the language learning task: experimental paradigms which compare this tendency to regularize in closely matched linguistic and non-linguistic tasks indicate stronger biases for regularity in language [9,10], suggesting that learners may expect language or communicative conventions more generally not to exhibit unpredictable variation (a point we return to in §4).…”
Section: Learningmentioning
confidence: 99%
“…A common hypothesis is that children's bias toward regularization might be due to their limited memory [46]. However, these accounts are hard to reconcile with other research indicating that limitations of this type do not necessarily lead to more regularization [7,8]; while it is possible that memory limitations may play a role, it seems unlikely that they are the main driving force behind this behaviour. Consistent with this, there is evidence that learners bring domain-specific biases to the language learning task: experimental paradigms which compare this tendency to regularize in closely matched linguistic and non-linguistic tasks indicate stronger biases for regularity in language [9,10], suggesting that learners may expect language or communicative conventions more generally not to exhibit unpredictable variation (a point we return to in §4).…”
Section: Learningmentioning
confidence: 99%
“…Hudson Kam and Chang () showed that the amount of regularization decreased when learners were given flashcards with words printed on them to reduce demands on lexical retrieval. Yet, conversely, manipulations designed to increase cognitive load did not increase regularization: When Perfors () tested adults under six different load conditions as they learned an artificial language with complex patterns of inconsistency (modeled after Hudson Kam & Newport, ), load groups were no more likely to regularize determiner use than a no‐load control group. Indeed, the data showed a nonsignificant trend in the opposite direction, with less regularization under concurrent load, counter to predictions of the Less‐Is‐More hypothesis.…”
Section: Empirical Evaluations Of the Less‐is‐more Hypothesismentioning
confidence: 99%
“…In such cases, the network may show effects of catastrophic interference where patterns of connectivity among hidden units become entrenched during learning, hindering subsequent learning that requires establishing a different pattern of connectivity. Further doubt about the benefits of capacity limitations comes from statistical models: Perfors () explored effects of capacity limitations by simulating learning as a process of Bayesian inference. She demonstrated that when capacity is diminished, regularization takes place only if an a priori bias toward regularization is present, which suggests that regularization is not a result of capacity limitations per se.…”
Section: Empirical Evaluations Of the Less‐is‐more Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this view, structure should emerge more readily in children than in adults during iterated language learning. However, it is not clear whether cognitive immaturity per se aids structure-inducing innovations as attempts to demonstrate experimentally that cognitive limitations lead to superior decomposition (Cochran, McDonald & Parault, 1999) or regularisation of input (Perfors, 2012a) have proved unsuccessful or are open to alternative interpretations (Perfors, 2012b;Rohde & Plaut, 1999;2003).…”
Section: Introductionmentioning
confidence: 99%